Correction: Post-functionalized iridium–Zr-MOF as a promising recyclable catalyst for the hydrogenation of aromatics. Issue 21 (11th October 2016) - Rasero-Almansa, Antonia M.; Corma, Avelino; Iglesias, Marta; Sánchez, Félix
Abstract : Correction for 'Post-functionalized iridium–Zr-MOF as a promising recyclable catalyst for the hydrogenation of aromatics' by Antonia M. Rasero-Almansa, et al., Green Chem., 2014, 16, 3522–3527.